2018
DOI: 10.1016/j.ijhydene.2018.10.192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fuel diversity in Solid Oxide Fuel Cell system

Abstract: Operability of Solid Oxide Fuel Cell (SOFC) on numerous fuels has been widely counted as a leading advantage in literature. In a designed system, however, switching from a fuel to another is not practically a straightforward task as this causes several system performance issues in both dynamic and steady-state modes. In order to demonstrate the system fuel diversity capabilities, these consequences must be well-evaluated by quantifying the characteristic measures for numerous fuel cases and also potential comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The simulator has already been validated against a real-life SOFC system rig approving its capability of a multi-scale performances capturing of the SOFC system. 30 The platform capability and fidelity for estimating the BoP mass and energy balances and the stack internal profiles have been demonstrated and validated in our previous research. 29 The simulated process flowsheet was selected to be rather comprehensive encompassing the main sub-processes of a SOFC plant including fuel conditioning, power generation through electrochemical process, depleted-fuel combustion and the heat recovery units that are the most likely elements of the system for the commercialization in short-term 31 .…”
Section: Sofc System Simulation Platformmentioning
confidence: 91%
“…The simulator has already been validated against a real-life SOFC system rig approving its capability of a multi-scale performances capturing of the SOFC system. 30 The platform capability and fidelity for estimating the BoP mass and energy balances and the stack internal profiles have been demonstrated and validated in our previous research. 29 The simulated process flowsheet was selected to be rather comprehensive encompassing the main sub-processes of a SOFC plant including fuel conditioning, power generation through electrochemical process, depleted-fuel combustion and the heat recovery units that are the most likely elements of the system for the commercialization in short-term 31 .…”
Section: Sofc System Simulation Platformmentioning
confidence: 91%
“…Solid oxide fuel cells (SOFCs) are perhaps the most interesting candidate for methane conversion [202]. One of the promising characteristics of SOFCs is their fuel flexibility [203]. Given the modest energy density of methane, other candidates should be considered for chemical hydrogen storage.…”
Section: Other Storage Methodsmentioning
confidence: 99%
“…Dey et al (2014) studied the influence of different types of biomass raw materials on the BG-SOFC system, and the results showed that bagasse showed the best performance in the mixed system. Amiri et al (2018) simulated the impact of fuel changes on the performance of the co-generation system by considering various fuel sources (such as natural gas, biogas, and syngas). The results show that fuel changes may seriously affect the consistency of the overall performance index of the system.…”
Section: Introductionmentioning
confidence: 99%